Novel validated method for GIS based automated dynamic urban building energy simulations. (15th November 2017) - Nageler, P.; Zahrer, G.; Heimrath, R.; Mach, T.; Mauthner, F.; Leusbrock, I.; Schranzhofer, H.; Hochenauer, C.
Abstract: The modelling of whole urban districts requires an automated process to parameterize simulation tools. This paper presents a validated methodology for fully automated building modelling within urban districts based on publicly available data. Dynamic building models with detailed heating systems are created in the simulation environment IDA ICE. The method of data collecting and processing and result visualization in a geographical information system (GIS) and the data storage procedure in a PostgreSQL database is described in detail. The building simulation model is validated with consumption data available from 69 buildings of the town Gleisdorf (Austria). The results of the annual heating and domestic hot water demand show a good approximation to the measurement data with a mean deviation of −0.98%. The urban simulation process was then extended to the whole community with its 1945 buildings. This method helps to model and quantitatively describe current building stock in an efficient and timesaving way and enables to develop future smart energy systems, in which the buildings interact with the district heating networks, with limited effort. Highlights: A methodology for automated dynamic urban building energy simulation is developed. The automation process is based on publicly available data. Both building model and heating system are automated modelled and dimensioned. A PostgreSQL database structure is created for building and heating system models. The urban simulation results are visualized in QGIS.